RESPONSABILITATEA PĂRINȚILOR ÎN EDUCAREA SPIRITUALĂ ȘI ACADEMICĂ A COPIILOR DUPĂ MODELUL LUI ISUS – INCLUSIV ÎN CONDIȚII DE CRIZĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The Responsibility of Parents in the Spiritual and Academic Education of Children after the Model of Jesus - Including in Crisis Conditions.Jesus is the model by which all parents should be guided, not only in the life of faith but also in the education they have to give their children. Jesus was a  man educated in the theological as well as the academic branch. He was  trained to know the written Torah as well as the oral Torah. Not only that, he  knew how to write, read and was able to speak several languages during his  time on earth. He is the role model for parents and children to copy.  Following the model of Jesus, the parent is responsible for educating the  child. He has the most important mission but also the greatest achievement  he can have.